Do Ownership and Culture Matter to Joint Venture Success? - Zhang, Yuan; Jing, Runtian; Fu, Wenhao (Journal of Comparative International Management, 2008)
Previous studies show that equity structure and cultural differences are important factors that influence the performance of joint ventures (JVs). Based on the JVs contract database and Import/Export ranking database the analysis shows that the performance of monopoly controlled JVs is better than others. However, cultural differences do not hinder performance; in fact, heterogeneity has provided better outcomes in JVs. Based on grouped data samples, it is believed that the higher the ratio of Chinese equity in JVs, the better the export performance. However, the relation between foreign equity and import orientation is not significant.